Improving Students’ Attitudes and Conceptual Understanding in Mathematics using Different Teaching Strategies - Nasayao, Roland A.; Lingo, Junar T. (International Journal of Membrane Science and Technology, 2023)
The study investigated the improvement of different teaching strategies on students' attitudes and conceptual understanding in Grade 11 Mathematics. It used a descriptive-correlational research design, and survey questionnaires were administered to the randomly selected students in the three senior high school classes of Surigao City National High School. Findings revealed that students' attitudes do not vary across the three approaches. Data further showed that the average rating scale of the students in terms of their grades is 86-89, which entails very satisfactory performance. Moreover, the level of students' attitudes is separate from improving conceptual understanding across the three strategies. Students' attitudes and conceptual understanding have no relationship except problem-based learning when compared to conceptual understanding. Hence, teachers' strategies in general math are associated with the student's attitudes toward learning mathematics.